A Whole Exome Study Identifies Novel Candidate Genes for Vertebral Bone Marrow Signal Changes (Modic Changes). Issue 16 (15th August 2017) - Kraatari, Minna; Skarp, Sini; Niinimäki, Jaakko; Karppinen, Jaro; Männikkö, Minna
Abstract : Study Design: A family-based study. Objective: The aim of this study was to identify rare genetic factors predisposing to Modic changes (MCs). Summary of Background Data: Lumbar disc degeneration (LDD) is one of the contributing factors behind low back pain (LBP). Lumbar MC visualized as bone marrow signal intensity changes on magnetic resonance imaging (MRI) represent a specific phenotype of LDD, which has a stronger association with LBP than LDD without MC. Methods: The study set consisted of two Finnish families: Family I included seven affected and four unaffected individuals and Family II eight affected and seven unaffected individuals. MCs were evaluated in 26 individuals using MRI. Whole exome sequencing was used to identify alleles cosegregating with MC. Annotate variation was used to carry out functional annotation of alleles and their frequencies were evaluated using 1000Genomes, Sequencing Initiative Suomi (SISu), and the Exome Aggregation Consortium (ExAC) databases. Results: We identified predisposing genetic alleles for MC in two Finnish families. In each family, only single allele cosegregated with MC. In Family I, the observed allele was an insertion and deletion in the HSPG2 gene, resulting in a premature termination codon. In Family II, a single nucleotide polymorphism (rs61753465) in the MAML1 gene was identified in all affected family members. Conclusion: We have identified two novel candidate genes, MAML1 and HSPG2, associating with MC. These genes are important in cartilage structure and joint cartilage maintenance. Our findings are novel among lumbar spine degenerative phenotypes. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text